"We Have to Try to Find a Way, a Clinical Bridge" - autistic adults' experience of accessing and receiving support for mental health difficulties: A systematic review and thematic meta-synthesis. (April 2022) - Brede, Janina; Cage, Eilidh; Trott, Joseph; Palmer, Lisa; Smith, Anika; Serpell, Lucy; Mandy, Will; Russell, Ailsa
Abstract: Co-occurring mental health difficulties among autistic adults are common and this association has implications for mental health services. Gaining a comprehensive understanding of autistic adults' experiences of accessing and receiving mental health support is a critical step to fully inform service provision. We conducted a systematic review and meta-synthesis of qualitative studies exploring autistic adults' mental health service experiences, triangulating the perspectives of autistic adults, clinicians and parents. Electronic database searches in MEDLINE, PsycINFO and Embase were conducted up to October 2021. This identified 10, 068 studies, of which 38 met study inclusion criteria. Using a thematic synthesis approach, we generated three superordinate analytical themes "Lonely, difficult service experience", "Complexity needs flexibility" and "Collaboration and empowerment", each with several subthemes. Our findings show that currently, mental health services do not adequately support autistic adults, and can even cause additional harm. There is a need for a more flexible, comprehensive and holistic approach, considering how being autistic affects the individual's mental health presentation and tailoring support to their needs. Building trusting relationships, listening to autistic adults, and empowering them to take agency, appear to be fundamental steps towards more successful mental health care provision. Highlights: Autistic adults have high rates of mental health needs. Studies show several barriers to accessing mental health support. Services should be adaptable to how mental health may differ in autism. Building trust, listening to and empowering autistic adults is fundamental. More research is needed to evaluate new treatments and autism-specific adaptations.